Maximum Ride, The Manga - Book 7 7 - Lee, NaRae; Patterson, James 1947-; Lee, JuYoun (New York : Yen Press, 2013)
Fang's blog highlights ITEX and their research, causing them to shut down, while Max goes to Antarctica to study the effects of global warming.
Keywords: Global warming -- Fiction; Kidnapping -- Fiction; Adventure and adventurers -- Fiction; Teenagers -- Fiction; Science fiction; Graphic novels; Adventure and adventurers -- Comic books, strips, etc; Global warming -- Comic books, strips, etc; Kidnapping -- Comic books, strips, etc; Teenagers -- Comic books, strips, etc; Science fiction comic books, strips, etc; Graphic novels